User evaluation of the University of the Philippines Diliman Interactive Learning Center (DILC) web repository and multimedia learning resources - Botictic, Marian L.; Cabbab, Johann Frederick A. (Quezon City : School of Library and Information Studies, University of the Philippines Diliman, 2009)
This study is a user evaluation of the Diliman Interactive Learning Center (DILC) web repository and the multimedia learning materials it contains. It is composed of three dimensions: (1) the evaluation of the level of awareness of the UP SLIS undergraduate students with the existence of the DILC website and its multimedia learning materials; (2) the evaluation of the level of accessibility of the DILC website; (3) and the level of acceptability of the Learning Objects contained in the DILC site.
A total of 44 undergraduate students of the School of Library and Information Studies (SLIS) were involved in the study to conduct a said self-rated evaluation of their awareness with the DILC site and their attitude towards the Learning Objects therein. In determining the level of accessibility of the DILC site, three automatic evaluation tools were used to: W3C Markup Validation Service, WAVE, and Site Valet 2.0.
The results of the study show that undergraduate students of the SLIS are actually familiar with the DILC website and the learning materials it has. However, when evaluated in terms of their access and usage of these materials, the students are still considered as less frequent users. With respect to their satisfaction and acceptance of the learning Objects, the students find the materials to be of quality, engaging, and good learning tools for students. It was concluded that even though the students are somewhat aware of the DILC's existence, they still ought to be informed and made aware of the DILC project, its products and services such that students could take more advantage of these learning tools for their learning. Having several multimedia learning materials and other services included in the website could perhaps give students, faculty, and other target users more help options for their learning. The fact that students agree of the positive learning value, quality, and engagement of learning objects and these materials, provision of these multimedia materials is certainly vital for students learning. But much more to the availability of these learning resources if the delivery mechanism it employs for the various types of multimedia learning materials. The accessibility of these materials could perhaps be more improved if the errors and missing elements in the pages will be addressed immediately using the detailed results generated from the different automatic evaluation tools as guide thereof.
Overall, the current progress and developments of the DILC indicates that further improvements and developments still ought to be performed for the project to be successful.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: University of the Philippines Diliman. Interactive Learning Resource Center (DILC).; Web sites -- Ratings